2018
DOI: 10.21475/ajcs.18.12.06.pne1090
|View full text |Cite
|
Sign up to set email alerts
|

Indirect estimation of leaf area in genotypes of 'Conilon' coffee (Coffea canephora Pierre ex A. Froehner)

Abstract: Leaf area is an important parameter in agronomic and physiological studies; thereby, the techniques used for its determination should be simple, fast and accurate. The objective of this study was to evaluate the efficiency of an equation for the indirect determination of leaf area in 'Conilon' (Coffea canephora) genotypes cultivated in the Western Amazon. The experiment was carried out in Porto Velho, Rondônia, in August and September 2011. It was arranged in a completely randomized 2 × 15 factorial design com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…According to Pimentel-Gomes (2009), all these values are considered high or very high, attesting high variability of the sampled data. However, it is desired a high CV value in works that seek a mathematical model to estimate the leaf area, since equations that take into account different leaves forms and sizes present better adjustments, besides representing all the stages of vegetative development of the plants (Toebe et al, 2011;Espindula et al, 2018;Pezzini et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…According to Pimentel-Gomes (2009), all these values are considered high or very high, attesting high variability of the sampled data. However, it is desired a high CV value in works that seek a mathematical model to estimate the leaf area, since equations that take into account different leaves forms and sizes present better adjustments, besides representing all the stages of vegetative development of the plants (Toebe et al, 2011;Espindula et al, 2018;Pezzini et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, models used to determine leaf area that takes into consideration only one linear dimension show lower degree of efficiency, being used only in a few cases. Thus, equations based on the set of dimensions and several leaves size, such as the product of the length by the width, are more desired for showing better adjusts for leaf area estimation (Espindula et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical models that aim the indirect leaf area estimation have been used for different plant species as cocoa (Asomaning & Lockard, 1963), Cucumis sativus L. (Cho, S. Oh, M. M. Oh, & Son, 2007), Vicia faca L. (Peksen, 2007), Tabebuia and Handroanthus (Monteiro et al, 2017), colza (Tian et al, 2017) and Coffea canephora (Schmildt, Amaral, Santos, & Schmildt, 2015;Espindula et al, 2018). Methods have been described to estimate leaf area of papaya from adult plants, as mentioned by Campostrini and Yamanishi (2001)…”
Section: Introductionmentioning
confidence: 99%
“…Observed leaf area (OLA) and estimated leaf area (ELA) of linear equations of first degree, quadratic and potential for the independent variables length (L), width (W) and product of length and width (LW), besides the value of p, mean absolute error (MAE), root mean square error (RMSE) and Willmott The use of only a linear dimension in practice is easier to execute, making the work less costly. However, these models are adjusted only for specific cases, being less precise for most species (Espindula et al, 2018). Therefore, models using the relation of linear dimensions as found in this study are notoriously used as reported for several species as Jatropha curcas (Pompelli et al, 2012), Vitis vinífera L. (Buttaro et al, 2015), Coffea canephora (Schmildt et al, 2015), Crotalaria juncea (Carvalho et al, 2017) and Litchi chinensis Sonn (Oliveira et al, 2017).…”
Section: Methodsmentioning
confidence: 99%